The Use of Kolb’s Model in Science Teaching Methodology - Močinić, Snježana (2020)
The relevance of this paper refers to the importance of Kolb’s model in developing future teachers’ professional competences and ability to integrate the theoretical and practical segment of their education. The aim of this paper is to examine what theoretical knowledge and practical experience is present in the Science Teaching Methodology regarding the initial teacher training in Croatia, in accordance with the Kolb’s model. The research was based on quantitative (descriptive analysis and factor analysis) and qualitative research methodology, which included the analysis of relevant literature and a survey conducted among the students of teacher education studies at the universities of Pula, Rijeka, Zadar and Split (Croatia). The results have shown that, in the given context, the Science Teaching Methodology is dominated by the acquisition of theoretical knowledge, lacking concrete experience activities and reflections on the real-life experience. Furthermore, innovations are only rarely introduced into teaching, which means that Kolb’s experiential learning model is not implemented in practice. The paper materials may be useful in the initial teacher training for acquiring the theoretical and practical knowledge about the use of Kolb’s model in the Science Teaching Methodology, and for integrating this model into the initial teacher training curriculum.